2018
DOI: 10.1016/j.apenergy.2018.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of ammonia resorption cycle for power generation by using novel composite sorbent

Abstract: Exploration of ammonia resorption cycle for power generation by using novel composite sorbent.Abstract: Expanded natural graphite and carbon coated nickel are selected as the additives in the development of novel composite sorbent. Improved thermo-physical properties of composite strontium chloride result in a faster sorption reaction rate than that without using carbon coated metal. A case study of ammonia-based resorption power generation cycle with two identical reactors is analyzed in terms of sorption cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…As stated in Section 3.1, a set of values considered as 'realistic' has been defined for the key simulation parameters: ηis = 0.8, ΔX = 0.8, τmet = 0.1, ΔTHX1 = 5 K, ΔTHX2 = 10 K and ΔTeq = 20 K. The results presented in Sections 4 and 5 were obtained under this 'real' set of parameters. However, since the existing literature on hybrid thermochemical cycles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] usually relies on more optimistic assumptions (especially for temperature pinches), a fair comparison of the performances of the proposed cycle with other hybrid thermochemical cycles cannot be provided. Therefore, another set of parameter values (more optimistic) has been defined and simulations have been carried out under this 'perfect' set of parameters: ηis = 1, ΔX = 1, τmet = 0, ΔTHX1 = 0 K, ΔTHX2 = 0 K and ΔTeq = 0 K. In this section, the results obtained under the 'perfect' set of parameters are reported and a comparison with the 'real' case is provided.…”
Section: Appendix a Computation Of Molar Heat Capacities Of The Reacmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated in Section 3.1, a set of values considered as 'realistic' has been defined for the key simulation parameters: ηis = 0.8, ΔX = 0.8, τmet = 0.1, ΔTHX1 = 5 K, ΔTHX2 = 10 K and ΔTeq = 20 K. The results presented in Sections 4 and 5 were obtained under this 'real' set of parameters. However, since the existing literature on hybrid thermochemical cycles [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] usually relies on more optimistic assumptions (especially for temperature pinches), a fair comparison of the performances of the proposed cycle with other hybrid thermochemical cycles cannot be provided. Therefore, another set of parameter values (more optimistic) has been defined and simulations have been carried out under this 'perfect' set of parameters: ηis = 1, ΔX = 1, τmet = 0, ΔTHX1 = 0 K, ΔTHX2 = 0 K and ΔTeq = 0 K. In this section, the results obtained under the 'perfect' set of parameters are reported and a comparison with the 'real' case is provided.…”
Section: Appendix a Computation Of Molar Heat Capacities Of The Reacmentioning
confidence: 99%
“…Jiang et al [22] studied another experimental setup of a resorption power and cold cogeneration cycle and their work highlighted the technical difficulty of achieving a stable power output due to strong coupling between chemical reaction kinetics and the dynamics of the expansion process. They went on to propose an improvement of resorption cycles using a novel composite sorbent [23], and obtained energy efficiencies in the range 0.11-0.14 and exergy efficiencies from 0.62 to 0.81, with a heat source temperature between 80°C and 110°C and a heat sink (ambient temperature) at 30 °C. Finally, their recent work [24] highlighted how hybrid thermochemical cycles hold promising potential for low-grade heat utilization: using heat source temperatures in the range 200-360°C and a heat sink temperature of 35°C, their novel resorption cycle integrating internal heat recovery provided a refrigeration effect at 0°C with a COP of 1.3 and exergy efficiencies between 0.41 and 0.74.…”
Section: Introduction and State-of-the-art Reviewmentioning
confidence: 99%
“… For power production only, a resorption cycle implementing a novel composite sorbent was investigated by Jiang et al [10]. Using hot source at 80-110 °C and heat sink at 30 °C, its energy and exergy efficiencies range from 0.07 to 0.12 and from 0.40 to 0.74, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The strontium chloride has been recommended as one of the promising chemisorption salt for low-grade heat recovery application and thermal energy storage [21,22]. For example, the authors have previously reported and investigated the potential application of using novel strontium chloride composite sorbent to form a power generation system [23]. Results indicated the developed system can be potentially used to recover low-grade heat sources such as solar energy, geothermal energy and industrial waste heat under the temperature over 120 o C [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the authors have previously reported and investigated the potential application of using novel strontium chloride composite sorbent to form a power generation system [23]. Results indicated the developed system can be potentially used to recover low-grade heat sources such as solar energy, geothermal energy and industrial waste heat under the temperature over 120 o C [23]. However, compared with the reported researches on composite CaCl2 [24], limited quantitative data can be found for the sorbents using strontium chloride (SrCl2), which leads to the difficulty of generating a highly accurate simulation model to predict the performance of sorption system using SrCl2 sorbents.…”
Section: Introductionmentioning
confidence: 99%